Effect of Hill Running and Circuit Training for Development of Aerobic Fitness among Marathon Runners of Telangana State in India - Rajesh Kumar (Universitas Negeri Semarang, 2023)
Abstract. Marathon is long distance running of 42.195 KM on road. Hill Running and Circuit Training are important training methods to develop Aerobic fitness among Marathon Runners. The Purpose of the study was to find Aerobic Fitness among Marathon Runners of Telangana State in India. Methods: Male Marathon Runners of Telangana State in India who participated in different Marathon events aged 25 to 30 Years were divided into three groups of fifteen each, experimental group of Hill running (n = 15) , Circuit Training group (n = 15) and a control group (n= 15). Both experimental groups trained on alternate days for twelve weeks 1 hour per session and control group underwent general training of Marathon on alternate days. Pre Test and Post Test were conducted among three groups for 12 Min Run Cooper Test to find the maximum distance covered in 12 Min. Results: The results of the study represented by mean and SD showed in pre and post-test a reading of 2391.83±102.57 2678.50±109.11 in hill training group with an F ratio of 129.92 at 0.000 level of confidence, whereas circuit training group with mean and SD of 2365.00±90.45 in pre 2518.30±79.78 in the post with F ratio of 129.92 significant at 0.000 level of confidence indicating that hill training group had noteworthy improvements in performance than circuit training and control groups. Circuit Training group also showed improvements. It is concluded that Hill Running is the good training method to develop the aerobic fitness. Abstract in Indonesia. Marathon adalah lari jarak jauh sejauh 42,195 KM on road. Hill Running dan Circuit Training adalah metode pelatihan penting untuk mengembangkan kebugaran aerobik di kalangan pelari maraton. Tujuan dari penelitian ini adalah untuk menemukan Kebugaran Aerobik di antara Pelari Maraton Negara Bagian Telangana di India. Pelari Maraton Pria dari Negara Bagian Telangana di India yang berpartisipasi dalam berbagai acara Maraton berusia 25 hingga 30 Tahun dibagi menjadi tiga kelompok masing-masing lima belas, kelompok eksperimen lari Bukit (n = 15), kelompok Pelatihan Sirkuit (n = 15) dan kelompok kontrol (n = 15). Kedua kelompok eksperimen dilatih pada hari-hari alternatif selama dua belas minggu 1 jam per sesi dan kelompok kontrol menjalani pelatihan umum Marathon pada hari-hari alternatif. Pre Test dan Post Test dilakukan pada tiga kelompok selama 12 menit Run Cooper Test untuk mengetahui jarak maksimum yang ditempuh dalam 12 menit. Hasil: Hasil penelitian yang diwakili oleh mean dan SD menunjukkan pada pre dan post-test pembacaan 2391,83±102,57 ; 2678,50±109,11 pada kelompok hill training dengan rasio F 129,92 pada tingkat kepercayaan 0,000, sedangkan kelompok pelatihan sirkuit dengan rata-rata dan SD 2365,00±90,45 di pra ; 2518,30±79,78 di pos dengan rasio F 129,92 signifikan pada tingkat kepercayaan 0,000 menunjukkan bahwa kelompok pelatihan bukit memiliki peningkatan kinerja yang patut dicatat daripada pelatihan sirkuit dan kelompok kontrol. Kelompok Pelatihan Sirkuit juga menunjukkan peningkatan. Disimpulkan bahwa Hill Running adalah metode pelatihan yang baik untuk mengembangkan kebugaran aerobik.